2021
DOI: 10.1111/pace.14424
|View full text |Cite
|
Sign up to set email alerts
|

S‐ICD screening revisited: do passing vectors sometimes fail?

Abstract: Introduction Pre‐implant ECG screening is performed to ensure that S‐ICD recipients have at least one suitable sensing vector, yet cardiac over‐sensing remains the commonest cause of inappropriate shock therapy in the S‐ICD population. One explanation would be the presence of dynamic variations in ECG morphology that result in variations in vector eligibility. Methods Adult ICD patients had a 24‐h ambulatory ECG performed using a digital Holter positioned to record all three S‐ICD vectors. Using an S‐ICD simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The concept of the potential varying of S‐ICD vectors eligibility over time was previously presented in a study by (Wiles et al, 2021). The study demonstrated that the vector score which determines S‐ICD eligibility is in fact dynamic in real‐life ICD population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of the potential varying of S‐ICD vectors eligibility over time was previously presented in a study by (Wiles et al, 2021). The study demonstrated that the vector score which determines S‐ICD eligibility is in fact dynamic in real‐life ICD population.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the potential varying of S-ICD vectors eligibility over time was previously presented in a study by (Wiles et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 10% of patients can fail this screening process in all 3 vectors, and up to 37% of passing vectors may fail upon rescreening. 9 , 10 This severely restricts the eligible patient population. Furthermore, the proportion shrinks dramatically when looking at patients who benefit the most from an extravascular device.…”
Section: Sensing Limitationsmentioning
confidence: 99%
“…The authors of this paper have previously introduced the concept of the potential varying of S-ICD vectors eligibility over time in a recently published study by Wiles et al which has demonstrated that the vector score which determines S-ICD eligibility is in fact dynamic in real-life ICD population. For that study, an S-ICD simulator provided by the device manufacturer was utilised for vector assessment [32]. The clinical significance for this dynamicity is not clear, but it sheds the light on the possibility that acquiring screening data over a much longer period than for conventional screening across the three S-ICD vectors can enable more reliable and descriptive screening of the vectors and can aid patient and vector selection in S-ICD candidates.…”
Section: Role Of Prolonged Screeningmentioning
confidence: 99%